Causes of the causes: Exploring Retention Among Canadian Midwives Utilizing Ecological Systems Theory - Elena Neiterman; Farimah HakemZadeh; Isik Zeytinoglu; Johanna Geraci; Bridget Beggs; Jennifer Plenderleigth; Derek Lobb (Elsevier, 2021)
Retention of health care professionals is a global concern, but the literature on this topic is dominated by empirical work. This article explores retention among midwives practising in Canada by utilizing Bronfenbrenner's ecological systems theory. Drawing on the interviews with 29 registered midwives across Canada, the article examines the applicability of the ecological systems theory to the analysis of workplace retention. It asserts that the interplay between psychosocial and macro-level factors shape midwives' work experiences and their decision to stay in the profession. This article contributes to the theoretical literature by demonstrating how ecological systems theory can be utilised to understand workplace transitions, especially the decision to stay in the profession.